Intercultural communication : pragmatics, genealogy, deconstruction - Young, R. E. (Robert E.), 1940- (Multilingual matters (Series), 1996)
In a world characterized by increased migration, travel, international co-operation and ethnic conflict, this volume reviews intercultural communication and action. Contributions from cultural anthropology, behavioural science, critical theory, philosophy and postmodern thought are examined.